2015
DOI: 10.1016/s2215-0366(15)00262-x
|View full text |Cite
|
Sign up to set email alerts
|

Bullying in the family: sibling bullying

Abstract: Original citation: Wolke, Dieter, Tippett, Neil and Dantchev, Slava. (2015) Bullying in the family : sibling bullying. The Lancet Psychiatry. Permanent WRAP url:http://wrap.warwick.ac.uk/67729 Copyright and reuse:The Warwick Research Archive Portal (WRAP) makes this work of researchers of the University of Warwick available open access under the following conditions. Copyright © and all moral rights to the version of the paper presented here belong to the individual author(s) and/or other copyright owners. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
148
4
27

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(194 citation statements)
references
References 91 publications
(81 reference statements)
12
148
4
27
Order By: Relevance
“…Parents should be engaged in anti-bullying programs and be educated to recognise the impact of their own behaviours and home environment. In addition, the link between inter-sibling aggression and peer bullying (Wolke, Tippett, & Dantchev, 2015) suggests interventions need to involve other family members.…”
Section: Discussionmentioning
confidence: 99%
“…Parents should be engaged in anti-bullying programs and be educated to recognise the impact of their own behaviours and home environment. In addition, the link between inter-sibling aggression and peer bullying (Wolke, Tippett, & Dantchev, 2015) suggests interventions need to involve other family members.…”
Section: Discussionmentioning
confidence: 99%
“…The findings add weight to the body of research that showed that the extent to which parents involve themselves in their children's disputes is likely to influence their children's sibling relationships (Brody, 1998;Smith & Ross, 2007). The findings also support the claims made by Tucker et al (2013) and Wolke et al (2015) that parenting programs may be a useful tool in promoting improved relationships among siblings. In support of Kramer's (2010) argument, and the findings from Tiedemann and Johnson (1992) the data emerging from this trial indicate how a parenting program can improve the sibling relationship by seeking to increase positive interactions among siblings, rather than focussing on reducing conflict.…”
Section: Discussionsupporting
confidence: 67%
“…Brody & Stoneman, 1987;Ralph et al, 2003). Furthere, destructive patterns of sibling conflict are linked with a myriad of troublesome social and behavioural problems (Kramer, 2004), including bullying (Wolke, Tippett, & Dantchev, 2015).…”
Section: Why Sibling Relationships Mattermentioning
confidence: 99%
“…Many subcategories have been identified including 'overt' and 'covert' acts of aggression [5]. A much-neglected area of bullying is sibling bullying, with a most recent review by Woke and colleagues [53] Many factors influence aggression and bullying [14]. The Media Research Lab at Iowa State University reports that they can predict children at high risk of bullying behavior 80% of the time based on the following three factors: boys, involved in a fight in the past year, and consumed a lot of media violence.…”
Section: Bullyingmentioning
confidence: 99%